Guidelines for mainstreaming natural river management in water sector investments. (Climate risk country profiles., 2021)
The NRM approach is designed to harness the natural functions of river systems so they sustainably provide important services such as water supply and flood and drought management. Drawing heavily on the concepts of ecosystem services, integrated water resources management, and integrated river basin management, NRM aims to harmonize nature based solutions and nonstructural measures with engineering interventions. This publication explains the value of NRM and provides step by step guidance on how the approach can be systematically integrated into water sector investments.